A Protein‐Like Nanogel for Spinning Hierarchically Structured Artificial Spider Silk. Issue 27 (3rd June 2022) - He, Wenqian; Qian, Dong; Wang, Yang; Zhang, Guanghao; Cheng, Yao; Hu, Xiaoyu; Wen, Kai; Wang, Meilin; Liu, Zunfeng; Zhou, Xiang; Zhu, Meifang
Abstract: Spider dragline silk is draw‐spun from soluble, β‐sheet‐crosslinked spidroin in aqueous solution. This spider silk has an excellent combination of strength and toughness, which originates from the hierarchical structure containing β‐sheet crosslinking points, spiral nanoassemblies, a rigid sheath, and a soft core. Inspired by the spidroin structure and spider spinning process, a soluble and crosslinked nanogel is prepared and crosslinked fibers are drew spun with spider‐silk‐like hierarchical structures containing cross‐links, aligned nanoassemblies, and sheath–core structures. Introducing nucleation seeds in the nanogel solution, and applying prestretch and a spiral architecture in the nanogel fiber, further tunes the alignment and assembly of the polymer chains, and enhances the breaking strength (1.27 GPa) and toughness (383 MJ m −3 ) to approach those of the best dragline silk. Theoretical modeling provides understanding for the dependence of the fiber's spinning capacity on the nanogel size. This work provides a new strategy for the direct spinning of tough fiber materials. Abstract : A fiber is draw‐spun from a soluble and crosslinked nanogel, and exhibits spider‐silk‐like hierarchical structures containing cross‐links, aligned nanoassemblies, and sheath–core structures. Introducing nucleation seeds, prestretch, and a spiral architecture in the nanogel fiber further tunes the alignment and assembly of the polymer chains, and enhances the breaking strength (1.27 GPa) and toughness (383 MJ m −3 ).